(untitled) (Nonconventional Technologies Review, 2022)
The objective of the article is to briefly detail the main aspects that can influence the productvity of a micro-EDM and 3D printing processes for processing an alloy of TiAl6V4. Electrical discharge machining (EDM) is one of the earliest non-conventional machining processes. EDM process use the thermoelectric energy between the the part and tool, which is an electrode manufactured from conductive materials. A pulse discharge occurs in a small gap filled with dielectric liquid between the work piece tool and removes material by melting and vaporising. This paper presents computerized modeling of the plant using Tecnomatix Siemens Plant Simulation.